International responsibility of the Peruvian State referred to the judgments of the Inter-American Court of Human Rights - Reyes Menéndez, Valeria (2016)
This event revolves around some relevant aspects regarding the responsibility of the State at the international level, such as the effectiveness of the judgments of the Inter-American Court of Human Rights and the position of Peru in this international entity.